Evaluation of Enterprise Content Management Components within the Example of Defense Industry Organization - Çakmak, Tolga; Külcü, Özgür (Information World, 2011)
Organizations tend to integrate the systems, such as document, records, web content and e-mail management that they develop for various purposes under enterprise content management. In this respect, the aim of this study is to analyze the current conditions and expectations of a defense industry organization in Turkey. According to this aim, the document management systems, electronic mail systems, Web content management applications used by the employees while running their day-to-day activities and the document/records systems used for official correspondence in 167 departments by 337 users within an organization specialized in defense industry in Turkey have been analyzed with a web based survey. Results show that the electronic mail management systems in the related organization are at a higher level than the other systems, and records management systems should be developed more than other analyzed systems. Implementation of an enterprise content management system and increasing the awareness of employees about enterprise content management are also recommended by the authors.